COMIC STRIP AS FINANCIAL LITERACY MEDIA: AUDIENCE PERSPECTIVES IN UNDERSTANDING INFLATION ISSUES - pamungkas, agus; hidayat, arif (Arty: Jurnal Seni Rupa, 2025)
Financial literacy is a crucial aspect of modern life. However, the younger generation often faces difficulties in understanding economic concepts. Comic strips come as an alternative media that is easier to access and understand, utilizing a combination of visuals and narration to convey information more effectively (Paivio, 1986). This study aims to assess the effectiveness of comic strips as well as the level of audience understanding of financial literacy. Using a qualitative approach with a case study method, this research analyzes audience acceptance of inflation-themed comic strips published through various digital platforms. Data was collected through observation, content analysis, and in-depth interviews with audiences who have read the comic strip. The results show that comic strips are effective in improving basic understanding of inflation, as they are able to simplify complex economic concepts. This is in line with McCloud's (1993) research, which states that comics can increase emotional engagement and appeal. However, the study also found that comic strips have limitations in conveying more in-depth information related to the technical aspects of inflation. This opinion is supported by Huston (2010), who asserts that optimal financial literacy requires a combination of various sources of information to achieve a more comprehensive understanding. Thus, this study contributes to the development of visual media-based financial literacy strategies.